(untitled) (Revista Contexto & Saúde, 2024)
This is a cross-sectional study with retrospective data collection that analyzed 356 patients admitted to a university hospital that serves as a reference for severe cases of COVID-19 during the first and second waves in Rio Grande do Sul, Brazil. Mortality was the outcome of interest, and significant variables were subjected to Poisson regression. Ninety-nine patients (27.8%) had death as an outcome. Low education, admission in poor general condition, malnutrition, lack of prior diagnosis of COVID-19, the presence of symptoms other than flu or respiratory symptoms, and polypharmacy were more common in patients who died. Reduced glomerular filtration rate, D-Dimer, C-reactive protein, urea, and elevated International Normalized Ratio were found upon hospital admission in patients who died. No differences were found in deaths between periods of the pandemic. After multivariate analysis, the factors related to death, in decreasing order of prevalence, were institutionalization, prolonged mechanical ventilation (>21 days) or for up to 21 days, high International Normalized Ratio on admission, age over 65 years, need for dialysis, and acute respiratory insufficiency. The results help to understand the behavior of the disease and provide support for training and resource allocation in scenarios of exponential care demands, such as outbreaks and epidemics.